PROYEKSI PENGEMBANGAN KOMODITAS KELAPA DALAM SECARA KEWILAYAHAN BERBASIS SUMBERDAYA LAHAN DALAM RANGKA MENDUKUNG PEMBANGUNAN PERKEBUNAN DI KALIMANTAN TENGAH - Bhermana, A; Prasetiyo, S, W; Irwandi I; Agustini, S. (AgriPeat, 2020)
In Central Kalimantan, the lands that has the potency for coconut development plantation still require systematic regional planning and appropriate land management in order to achieve optimum prodution. The development of coconut as one of the prime commodities in Central Kalimantan is required to contribute national export needs. The objective of this study was to design spatial planning concept for coconut commodity development based on land resource in Central Kalimantan. The procedure of land suitability evaluation approach and GIS application was used in this study to assess crop suitability that is integrated in spatial nformation system. The results land evaluation showed that land suitability class for coconut is class S3 (marginally suitable) with limiting factors including presence of peat, drainage, nutrient availability, soil acidity, and slope. The results of further spatial analysis explain that the potential areas for the coconut commodity development in Central Kalimantan is ??3,499,712 Ha or 22.65% of the total areas. Spatially, the potential of development areas are spread within almost every district. There are 2 areas that is not designated for coconut development, namely the city of Palangka Raya and Murung Raya regency due to limiting factors existence such as sandy soil type and steep slope (> 30%). Regional development strategies for coconut commodities can then be allocated to areas that have abandoned land areas. While at areas surrounding by settlements, they can be implemented by the use intercropping farming systems at the age of coconut growth for less than 3 years in order to optimize the land resources and climate productivity while at the same time increasing the income